Income, Wealth, and Environmental Inequality in the United States - Jonathan Colmer; Suvy Qin; John Voorheis; Reed Walker (CESifo GmbH, 2024)
This paper explores the relationships between air pollution, income, wealth, and race by combining administrative data from U.S. tax returns between 1979–2016, various measures of air pollution, and sociodemographic information from linked survey and administrative data. In the first year of our data, the relationship between income and ambient pollution levels nationally is approximately zero for both non-Hispanic White and Black individuals. However, at every single percentile of the national income distribution, Black individuals are exposed to, on average, higher levels of pollution than White individuals. By 2016, the relationship between income and air pollution had steepened, primarily for Black individuals, driven by changes in where rich and poor Black individuals live. We utilize quasi-random shocks to income to examine the causal effect of changes in income and wealth on pollution exposure over a five year horizon, finding that these income–pollution elasticities map closely to the values implied by our descriptive patterns. We calculate that Black-White differences in income can explain ∼10 percent of the observed gap in air pollution levels in 2016.
Keywords: H00; H40; Q50; R00; 330; income; wealth; air pollution; inequality